Multibias and temperature dependence of the current‐gain peak in GaN HEMT. Issue 4 (7th January 2020) - Alim, Mohammad A.; Hasan, Muhammad A.; Rezazadeh, Ali A.; Gaquiere, Christophe; Crupi, Giovanni
Abstract: Thermal and multibias behavior of the peak in the short‐circuit current‐gain ( h 21 ) has been investigated for a GaN HEMT, aiming to contribute to an extensive knowledge on it. To obtain a simple and complete insight of this phenomenon and its influence in device performance over operating conditions, high‐frequency multibias scattering ( S ‐) parameter measurements have been analyzed from low to high temperature. It has been observed that the current‐gain peak might get to be more or less serious depending on the working circumstances. The peak affecting h 21 has been successfully reproduced by using an equivalent‐circuit model. Moreover, a novel procedure has been developed to interpret this kind of phenomenon by quantifying the area of the current‐gain peak (ACGP), which is denoted as the area corresponding to h 21 curves with and without the peak. It is found that the ACGP is strongly dependent on bias and less dependent on temperature. The relevance of a comprehensive evaluation of the peak in h 21 lies in its usefulness for empowering RF engineers to efficiently consider it for both device modeling and circuit design.